Sternal resection and reconstruction due to sternal destruction caused by malignancy: a case report - Imam Cesyo, Giadefa; Sudarma, I Wayan (Indonesian Vascular Access Association (IVAA), 2025)
Introduction: Sternal resection and reconstruction are uncommon chest wall procedures but can pose significant challenges in their management. Sternal resection may lead to thoracic cavity instability, making careful patient selection followed by an appropriate reconstruction technique. Case: We report a case of sternal resection and reconstruction using reconstruction plates and hernia mesh. A 21-year-old male presented with a rapidly growing anterior chest wall mass, increasing in size over three months prior to surgery. The mass measured 15 x 10 x 8 cm, was firm, and fixed. A CT scan revealed an irregular solid mass originating from the sternum, with destruction of the sternal bone. A procedure was performed involving the resection of anterior chest wall and reconstruction using reconstruction plates and hernial mesh. The resection of large portions of the chest wall poses complex challenges due to technical difficulties, surgical complications, and respiratory failure caused by chest wall instability and paradoxical movements. Four types of sternal defects are generally defined: partial longitudinal sternectomy > 75% of the sternal width, subtotal lower, subtotal upper, and subtotal mid sternectomy. Full reconstruction is generally indicated for resections involving the entire width of the sternum. Various techniques have been proposed, including myocutaneous flaps, the use of mesh and patches supplemented with methacrylate composites, titanium mesh, autograft or allograft bone, and prosthetics. However, no standardized technique exists. The choice of technique is largely based on the surgeon’s experience. This report describes a relatively simple technique using readily available and economical prostheses to achieve a functionally stable chest wall. In this case, total mid-sternectomy was performed, followed by reconstruction using two reconstruction plates placed transversely on the second and third ribs, with hernia mesh beneath. The patient was extubated 24 hours postoperatively, although minimal paradoxical movements were observed without accompanying respiratory difficulty. Conclusion: Reconstruction plates and hernia mesh can maintain respiratory mechanics but require refinement to improve chest wall stability and protective function against external trauma.